APPLICATION OF THE ADDIE MODEL IN DEVELOPING ETHNOSCIENCE BASED SCIENCE LEARNING VIDEO MEDIA OF PEJATEN POTTERY CRAFTS TO IMPROVE CRITICAL THINKING SKILLS - Gusti Ayu Putu Alit Wistari; Ni Nyoman Lisna Handayani; Gusti Ngurah Arya Yudaparmita (El Midad, 2026)
Students' critical thinking skills can be optimally honed through a learning process supported by teaching materials relevant to their surrounding environment. Integrating science concepts with local wisdom (ethnoscience), such as Pejaten pottery crafts, can help students understand science phenomena concretely. This study aims to analyze, develop, and test the feasibility and effectiveness of ethnoscience based video learning media on the topic of Force using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The method used is Research and Development (R&D) with quantitative and qualitative descriptive approaches. The results showed that: 1) The Analysis stage found a low understanding of force concepts and a lack of interactive media; 2) The Design stage produced a Canva based video design that combines force materials with the pottery making process; 3) The Development stage showed that the media is highly feasible, obtaining a validation score of 88% from material experts and 90% from media experts; 4) The Implementation stage in a limited trial received a highly positive student response of 92%; 5) The Evaluation stage proved an improvement in students' critical thinking skills with an N-Gain score of 0.65 (medium category). Based on these results, the ethnoscience based learning video media of Pejaten pottery crafts is proven to be feasible, practical, and effective in improving students' critical thinking skills.